New records of late Holocene tephras from Lake Futalaufquen (42.8°S), northern Patagonia. (March 2016) - Daga, Romina; Ribeiro Guevara, Sergio; Arribére, María
Abstract: In regions with limited knowledge of the historical volcanic record, like remote areas in the Andean Southern Volcanic Zone, the definition of reliable age-depth models for lake sequences represents a valuable tool for tephra layers dating. In Lake Futalaufquen (42.8°S), Northern Patagonia, a short sedimentary sequence was extracted after the AD 2008 Chaitén eruption with the purpose to analyze the records of volcanic eruptions at these poorly studied latitudes. The sequence was dated by 210 Pb, 137 Cs, and 14 C techniques. Five tephras were identified for the last 1600 years, restricted to the last 5 centuries. Sedimentology, morphology, and geochemical properties allowed the characterization of the tephras and their correlation with tephras recently identified proximal to the sources, mainly from Chaitén and Huequi volcanoes, and Michinmahuida accessory cones, representing the first distal records reported of these tephras. Furthermore, tephras modeled ages obtained by the sequence age-depth model shrink the ages for the volcanic events, like a potential cycle of activity from Michinmauida accessory cones during AD 1530 ± 55, one eruption from Huequi volcano at AD 1695 ± 50, and a possible recent eruption from Chaitén at AD 1775 ± 40. Additionally, the work contributes to improve the regional volcanic records knowledge, basic for volcanic hazard assessment. Graphical abstract: Highlights: A short sedimentary sequence from L. Futalaufquen (42.8°S), Patagonia, was studied. The sequence was dated by 210 Pb, 137 Cs, and 14 C techniques, covering 1600 years. 5 tephras were characterized by sedimentology, morphology and geochemistry. Tephra sources were Chaitén and Huequi volcanoes, and Michinmahuida accessory cones. They represent the first distal reports of recently identified proximal tephras.